Career Counseling in an Industrial Society - Super, Donald E. (Canadian Journal of Counselling and Psychotherapy, 2012)
A post-industrial society is a society in which leisure plays a more important role in life than does work as cybernation releases people from routine employment. People in higher-level occupations are freed to concentrate on the more intellectually demanding aspects of their work; others are freed for luxury crafts, service, or leisure activities. At the same time, some young people are rejecting the established work ethic. The counter cultures of history are briefly reviewed, and the conclusion is drawn that systematic effort of some kind is sought by most people, who feel the need for respected roles and for self-fulfillment in such roles. The extent to which leisure as it has generally been used, and as it is used now, can fulfill these needs is examined. The construct "career" is reviewed, and its implications for the multifaceted career counseling made necessary by a post-industrial society are considered. Career counseling is redefined to make it include consideration of ways in which people may, during the course of a lifetime, find outlets for their aptitudes and interests in activities which may be vocational or avocational.